Dissection of Microbial Community Functions during a Cyanobacterial Bloom in the Baltic Sea via Metatranscriptomics - Berg, Carlo; Dupont, Chris L.; Asplund-Samuelsson, Johannes; Celepli, Narin A.; Eiler, Alexander; Allen, Andrew E.; Ekman, Martin; Bergman, Birgitta; Ininbergs, Karolina (Frontiers in Marine Science, 2018)
Marine and brackish surface waters are highly dynamic habitats that undergo repeated seasonal variations in microbial community composition and function throughout time. While succession of the various microbial groups has been well investigated, little is known about the underlying gene-expression of the microbial community. We investigated microbial interactions via metatranscriptomics over a spring to fall seasonal cycle in the brackish Baltic Sea surface waters, a temperate brackish water ecosystem periodically promoting massive cyanobacterial blooms, which have implications for e.g. primary production, nutrient cycling, and expansion of hypoxic zones. Network analysis of the gene expression of all microbes from 0.22 - 200 µm in size and of the major taxonomic groups dissected the seasonal cycle into four components that comprised genes peaking during different periods of the bloom. Photoautotrophic nitrogen-fixing Cyanobacteria displayed the highest connectivity among the microbes, in contrast to chemoautotrophic ammonia-oxidizing Thaumarchaeota, while heterotrophs dominated connectivity among pre- and post-bloom peaking genes. The network was also composed of distinct functional connectivities, with an early season balance between carbon metabolism and ATP synthesis shifting to a dominance of ATP synthesis during the bloom, while carbon degradation, specifically through the glyoxylate shunt, characterized the post-bloom period, driven by Alphaproteobacteria as well as by Gammaproteobacteria of the SAR86 and SAR92 clusters. Our study stresses the exceptionally strong biotic driving force executed by cyanobacterial blooms on associated microbial communities in the Baltic Sea and highlights the impact cyanobacterial blooms have on functional microbial community composition.